COMPLEX TYPES OF SPEECH PATHALOGY BASED ON PSYCHOLINGUISTIC ANALYSIS - Rimbayeva Ozoda Bazarbayevna (Web of Journals Publishing, 2024)
This article provides information on the most complex types of speech patalogies based on psycholinguistic analysis and on the work carried out in the process of their correction. Psycholinguistic analysis evaluates speech defects such as Alalia, aphasia, incomplete speech development, and dysarthria as the most complex speech defects.
Keywords: Psycholinguistics, patalogy, alalia, aphasia, dysarthria, dyslalia, speech.